Neurological manifestations of post-acute sequelae of COVID-19: which liquid biomarker should we use? - Comeau, Dominique; Martin, Mykella; Robichaud, Gilles A.; Chamard-Witkowski, Ludivine (Frontiers in Neurology, 2023)
Long COVID syndrome, also known as post-acute sequelae of , is characterized by persistent symptoms lasting 3-12 weeks post SARS-CoV-2 infection. Patients suffering from PASC can display a myriad of symptoms that greatly diminish quality of life, the most frequent being neuropsychiatric. Thus, there is an eminent need to diagnose and treat PASC related neuropsychiatric manifestation (neuro-PASC). Evidence suggests that liquid biomarkers could potentially be used in the diagnosis and monitoring of patients. Undoubtedly, such biomarkers would greatly benefit clinicians in the management of patients; however, it remains unclear if these can be reliably used in this context. In this mini review, we highlight promising liquid (blood and cerebrospinal fluid) biomarkers, namely, neuronal injury biomarkers NfL, GFAP, and tau proteins as well as neuroinflammatory biomarkers IL-6, IL-10, TNF-α, and CPR associated with neuro-PASC and discuss their limitations in clinical applicability.